Preparation and characterizations of antibacterial–antioxidant film from soy protein isolate incorporated with mangosteen peel extract - Zhou Xin (De Gruyter, 2021)
The mangosteen peel extract (MPE) was used to obtain soy protein isolate (SPI) films. The results show that MPE exhibited a high content of total phenolics and antioxidant activity. Moreover, the MPE can enhance the antibacterial–antioxidant properties, UV-visible light barrier properties, and water-resistant properties of the SPI films. The presence of MPE resulted in an increase in water vapor permeability and hydrophobicity. The extract addition also reduced the film’s crystallinity along with a decrease in the mechanical property and lowering of the maximum degradation temperature. Attenuated total reflectance Fourier transform infrared spectroscopy revealed that the polyphenols in MPE could interact with SPI through hydrogen bonds and hydrophobic interactions, and the addition of MPE changed the secondary structure of SPI with a decrease in β-sheets and an increase in β-turns and random coils. Scanning electron microscopy showed that all the films exhibited smooth and homogenous morphology on the surface and on some layers through cross-sectional images. Our results suggested that the MPE would be a promising ingredient to make SPI films used as an active packaging material.